Keluhan Gangguan Kulit pada Pemulung Wanita Di Tempat Pembuangan Akhir (TPA) Terjun - Ferusgel, Agnes; Nasution, Rina Mahyurni; Butar-Butar, Maria (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2018)
Female scavengers at Terjun Landfill when working are still found who have not used a complete PPE and are still lacking in personal hygiene, this can cause health problems, one of which is complaints of skin disorders such as itching, redness, and burning. The hypothesis in this study is that there is a relationship between working period, personal hygiene, and the use of PPE with complaints of skin disorders in female scavengers at TPA Falls. This research is an analytic observational survey research with cross-sectional approach. The population and sample in this study were all 53 female scavengers carried out at the Terjun Landfill in Marelan, Medan. Analysis of the data used is a multiple linear regression test. The results showed that there was a relationship between personal hygiene (p = 0.022) and PPE use (P = 0.025) with complaints of skin disorders in female dwellers at Terjun Landfill Marelan, while there was no relationship between work expectations with complaints of skin disorders in female scavengers. The results showed the need for cross-sectoral cooperation to improve the health status of scavengers, one of which was by conducting socialization on occupational safety and health, including in terms of personal hygiene at work and the importance of using PPE for scavengers.